Bioseguridad en explotaciones porcinas : bioseguridad en hatos porcinos de Antioquia, Colombia (1999)
ABSTRACT: This review includes current information of health assurance and addresses the Colombian situation by a survey we did perform. Biosecurity is more strictly implemented from the top to the bottom farms of the swine production pyramid to maximize herd's health status. In this process, the farms invest time, money and labor, to keep herds away from specific pathogens, to offer good quality product to breeding stock and pork markets. Any swine herd has to establish its own biosecurity policies according with the type of specific pathogens present, within it.